Osebnostne poteze kot napovedniki socialnega prilagajanja otrok ob vstopu v šolo - Zupančič, Maja (Psihološka obzorja (Ljubljana), 2008)
Contemporaneous and longitudinal predictive relations between three blocks of predictors and measures of children's social adjustment (social competence, internalizing and externalizing behaviour) after the school entry were investigated. The first block of predictors captures expressions of child personality dimensions as perceived by pre-school teachers/assistant school teachers, the second block contains parental education and self-evaluations of parenting in mothers and fathers of the target children, and the third block refers to children's pre-school attendance prior to school entry. Using the Social competence and behavior evaluation scale, school teachers reported on firstgraders' social adjustment. The Inventory of child individual differences was employed to assess personality when target children were 3, 4, 5 and 6 years old, while at ages 3 and 6 their parents filled-in the Familyenvironment questionnaire to provide self-reports on parenting. The blocks of predictors jointly explain a relatively large portion of variance in firstgraders' social adjustment both contemporaneously and longitudinally. Personality characteristics significantly predict all of the criteria measures, while family environment and pre-school attendance explain additional variance in internalizing behaviour (depressive, anxious, isolated,and dependent behaviour), over and above the contribution of personality. Perceptions of children's conscientiousness-openness at the beginning of the school year as well as through early childhood and of their agreeableness in preschool predict teacher ratings of the firstgraders' social competence. Externalizing behaviour (angry, aggressive, egotistical and oppositional behaviour) was consistently predicted by low conscientiousness-openness, extraversion-emotional stability, and low agreeableness. Finally, low conscientiousness-openness in school, low extraversion-emotional stability in preschool, maternal inefficient control of the firstgraders' behaviour, low education of the father and absence of children' previous pre-school experience predicted internalizing behaviour.
Keywords: osebnostne lastnosti; otroci; child; socialno prilagajanje; vstop v šolo